Neuropharmacokinetic evaluation of lactoferrin-treated indinavir-loaded nanoemulsions: remarkable brain delivery enhancement. (4th May 2019) - Karami, Zahra; Saghatchi Zanjani, Mohammad Reza; Rezaee, Saeed; Rostamizadeh, Kobra; Hamidi, Mehrdad
Abstract: Objective: Indinavir (IDV), an antiretroviral protease inhibitor used in treatment of HIV infection, has limited entry into brain due to efflux by the P-glycoprotein presented in blood–brain barrier. The aim of present study was to develop lactoferrin-treated nanoemulsion containing indinavir (Lf-IDV-NEs) for delivery to brain. Methods: Indinavir-loaded nanoemulsions (IDV-NEs) were prepared by high-speed homogenization method, and then lactoferrin was coupled to IDV-NEs by water soluble EDC method. Results: The hydrodynamic diameters, polydispersity index, and zeta potential of IDV-NEs were 112 ± 3.5 nm, 0.20 ± 0.02, and −33.2 ± 2.6 mV, respectively. From in vivo studies in animal model of rats, the AUC0–4 h of brain concentration–time profile of IDV-NEs and Lf-IDV-NEs were 1.6 and 4.1 times higher than free drug, respectively. The brain uptake clearance of IDV-NEs and Lf-IDV-NEs were, interestingly, 393- and 420-times higher than the free drug. Conclusions: It can be concluded that applying both lactoferrin-treated and non-treated nanoemulsions clearly leads to significant brain penetration enhancement of indinavir, an effect which is more pronounced in the case of Lf-IDV-NEs with the higher drug residence time in brain.